P380 Intelligence is predicted by single-vs-double-sensory brain responses. Issue 9 (September 2017) - Horwitz, Anna; Klemp, Marc; Horwitz, Henrik; Thomsen, Mia Dyhr; Rostrup, Egill; Mortensen, Erik Lykke; Osler, Merete; Lauritzen, Martin; Benedek, Krisztina
Abstract : Objective: This research investigated the association between intelligence test scores and gamma-range steady-state power-responses (SS-PR) to an auditory, a visual, and a combined audiovisual stimulation. We hypothesized, and established empirically, that the difference in SS-PR from the mono-modal to the bimodal stimulation ( Δ P) is associated with intelligence. Methods: We measured SS-PR as well as intelligence and other aspects of neurocognitive function in 36 healthy males born in 1953 who were a part of a Danish birth cohort study. Results: We found a highly significant correlation between intelligence and the difference in SS-PR from the mono-modal to the bimodal stimulation ( Δ P). The findings were robust to controlling for size-at-birth measures, length of education, speed of processing as well as a range of other potentially confounding biomarkers. Interestingly, we found that intelligence scores measured at earlier points in time, namely in childhood, youth, and late midlife, also were significantly associated with Δ P. Finally, we found that Δ P has a sensitivity of 81% of detection of an intelligence score below the average. Discussion: Our findings suggest that the uncovered relationship between intelligence and Δ P represents a constitutive relationship. Furthermore, our results are consistent with the notion that intelligence is related to the efficiency of the brain, and provide support for Haier's efficiency hypothesis. Conclusion: Δ P reflects intelligence throughougt life. Significance: Our results indicate that Δ P may be useful as a supplement to cognitive neuropsychological testing.